'Bureaucratic Attitudes'—an Intermediary Variable of Policy Performance. (December 2014) - Goel, Sangeeta
Traditionally, a policy-making exercise is regarded to be a mechanical process comprising well-defined steps and it is presumed that if those are taken care of, a sound policy is put in place. These key steps normally include—(a) problem identification, (b) selection of the policy options from the given basket of choices, (c) implementation by the available public agency, (d) monitoring and feedback and (e) review and rectification. Of late, policy makers have started focusing on the stakeholders, the deadlines and the media management too. However, in this 'linear rational' view of policy making, 'the element' which though involved from beginning to the end yet normally given a miss is the 'human factor'. Interestingly, this 'human factor' or 'the agency' does not happen to be a mere 'complex grouping of cells' or 'an automated robot'. According to psychologists, this 'mammalian agency' might carry an endless emotional, intellectual and psychological baggage which according to my research insight is capable of impacting the entire policy process often in unintended and unforeseen ways. This, in Indian context, has significant dimensions since it is a pluralistic society and every individual carries a plethora of social identities, namely, caste, sub-caste, class, ethnicity, creed, language, religion, gender, rural–urban and constitutional status, etc. These multiple identities often supersede or come in clash with the national identity and in turn might come in the way of 'public interest'. This article, therefore, takes a look at how in real world, this psychological baggage or attitudes of human agency might interfere with the policy process at implementation level, distorting the entire policy outcome. The methodology adopted is that of an ethnographic case based analysis located in an Indian public organization. Taking a cue from existing literature and prominent policy frameworks and adopting select qualitative research tools, an inferential analysis is done to inform the research question — 'How bureaucratic attitudes can mess up with policy implementation to defeat the very purpose of an otherwise well-intended policy?'